Comparisons of the humoral and cellular immunity induced by live A16R attenuated spore and AVA-like anthrax vaccine in mice. (March 2017) - Lv, Jin; Zhang, Ying-ying; Lu, Xun; Zhang, Hao; Wei, Lin; Gao, Jun; Hu, Bin; Hu, Wen-wei; Hu, Dun-zhong; Jia, Na; Feng, Xin
Abstract: The live attenuated anthrax vaccine and anthrax vaccine adsorbed (AVA) are two main types of anthrax vaccines currently used in human. However, the immunoprotective mechanisms are not fully understood. In this study, we compared humoral and cellular immunity induced by live A16R spore vaccine and A16R strain derived AVA-like vaccine in mice peripheral blood, spleen and bone marrow. Both A16R spores and AVA-like vaccines induced a sustained IgG antibody response with IgG1/IgG2b subtype dominance. However, A16R spores vaccine induced higher titer of IgG2a compared with AVA-like vaccine, indicating a stronger Th1 response to A16R spores. Using antigen-specific ELISpot assay, we observed a significant response of ASCs (antibody secreting cells) and IL4-CSCs (cytokine secreting cells) in mice. Specially, there was a positive correlation between the frequencies of antigen specific ASCs and IL4-CSCs in bone marrow derived cells, either by A16R spore or AVA-like vaccine vaccination. Moreover, we also found A16R spore vaccine, not AVA-like vaccine, could induce sustained frequency of IFN-γ-CSCs in bone marrow derived cells. Collectively, both the vaccines induced a mixed Th1/Th2 response with Th2 dominance in mice and A16R spore vaccine might provide a more comprehensive protection because of humoral and cellular immunity induced in bone marrow.